Chiral Chalcogenyl‐Substituted Naphthyl‐ and Acenaphthyl‐Silanes and Their Cations. Issue 69 (27th October 2020) - Künzler, Sandra; Rathjen, Saskia; Rüger, Katherina; Würdemann, Marie S.; Wernke, Marcel; Tholen, Patrik; Girschik, Corinna; Schmidtmann, Marc; Landais, Yannick; Müller, Thomas
Abstract: Cyclic silylated chalconium borates 13 [B(C6 F5 )4 ] and 14 [B(C6 F5 )4 ] with peri ‐acenaphthyl and peri ‐naphthyl skeletons were synthesized from unsymmetrically substituted silanes 3, 4, 6, 7, 9 and 10 using the standard Corey protocol (Chalcogen Ch=O, S, Se, Te). The configuration at the chalcogen atom is trigonal pyramidal for Ch=S, Se, Te, leading to the formation of cis ‐ and trans ‐isomers in the case of phenylmethylsilyl cations. With the bulkier tert ‐butyl group at silicon, the configuration at the chalcogen atoms is predetermined to give almost exclusively the trans ‐configurated cyclic silylchalconium ions. The barriers for the inversion of the configuration at the sulfur atoms of sulfonium ions 13 c and 14 a are substantial (72–74 kJ mol −1 ) as shown by variable temperature NMR spectroscopy. The neighboring group effect of the thiophenyl substituent is sufficiently strong to preserve chiral information at the silicon atom at low temperatures. Abstract : The Corey reaction of acenaphthyl‐ and naphthyl‐based chiral silanes allows the synthesis of silylchalconium ions with control of the stereochemistry at the chalcogen atom (shown here for the sulfonium ion). The chalcogen neighboring group effect on the silyl cation is sufficiently strong to conserve the stereochemistry in a consecutive nucleophilic attack.